CONCEPT OF INTERNAL AND EXTERNAL MAGNETIC INFLUENCES OF NATURE ON LIVING WORLD ORGANISMS - Guzal Davlatovna Majidova (Web of Journals Publishing, 2024)
Nowadays, humanity is under the influence of many factors, including the external environment, ecology, and the like. In this case, along with the human psyche, changes can be observed in its body. That is, changes in the amount of microelements in the body, such as their violation, are a serious problem for humanity. In such a situation, the changes occurring in the human organism require the study of the functions of living organisms, the currents existing in it, and the forces of influence.
Keywords: magnetosphere, current, chemical elements.